Association of transferrin genotypes and production traits of Holstein-Friesian cows in Vojvodina - Dragomir Lukač; Vitomir Vidović; Nemeš Žolt; Attila Zsolnai; Milena Stevanović; Beáta Bán (Mljekarstvo)
The aim of this study was to identify genotypes of transferrin, evaluate their frequency in popula¬tion of Holstein-Friesian cows, and to study association of transferrin genotypes with productivity of cows. Blood samples were collected from 249 healthy adult Holstein cows, daughters of 18 sires, reared at farm in Vojvodina. The nine transferrin (Tf) genotypes were identified: three (transferrin AA, D1D1 and D2D2) of these were homozygous and the remaining six (transferrin AD1, AD2, AE, D1D2, D1E and D2E) heterozygous. The frequencies of genotypes AD2, D1D2, D2D2 and AD1 were 0.29, 0.20, 0.17, and 0.11, respectively, while the other genotypes had frequencies below 0.11. The frequency of alleles A, D1, D2 and E, which was derived from the frequency of genotypes, was 0.30 for allele A, 0.19 for allele D1, 0.45 for allele D2 and 0.06 for allele E. In the analyzed population, cows Tf genotype D2E, AD2, D2D2, and D1D2 had the highest average of milk and milk fat yield in the first three standard lactation, while cows genotype AA, AD1 and D1E had the least amount. Analysis of variance showed that Tf genotype had a non-significant effect in the case of milk fat. However, cows which showed the highest performance for milk fat yield in three standard lactations were phenovarients Tf D2E, AD2, D2D2 and D1D2 in the analyzed population. Based on these results, the general conclusion can be made that the cows with Tf genotype AD2 recorded best results in all observed traits, and that cows which were heterozygous for Tf gene had higher milk yield and milk fat than the cows homozygous for Tf gene.